Does Corporate Governance Matter in Decision Making of Stock Repurchases? - Herdiani, Aulia (Universitas Negeri Malang, 2022)
This research highlights the motivation of stock repurchase in Indonesia and how corporate governance influences the decision making to perform stock repurchases. Each country has different motivation to repurchase stocks. This study examines the motivation based on six stock repurchase hypotheses. Further, this study examines the interaction effect of both mechanisms. The data of stock repurchase were collected manually from the corporate events issued by the companies. The test is carried out based on two corporate governance mechanisms, internal and external mechanisms, which have different tendencies in the corporate governance supervision system. Based on the analysis results, stock repurchase in Indonesia is motivated to maintain the sustainability of the authority of the shareholders, especially due to fluctuated economic conditions.